Globally Attractive Mild Solutions for Non-Local in Time Subdiffusion Equations of Neutral Type - Lizama-Yanez, C; Gonzalez-Camus, J (Juliusz Schauder Center for Nonlinear Analysis, 2020)
We prove the existence of at least one globally attractive mild solution to the equation (Formula presented), under the assumption, among other hypothesis, that A is an almost secto-rial operator on a Banach space X and the kernel b belongs to a large class, which covers many relevant cases from physics applications, in particular the important case of time-fractional evolution equations of neutral type. © 2020 Juliusz Schauder Centre for Nonlinear Studies Nicolaus Copernicus University in Toruń.